2023
DOI: 10.1186/s12888-023-04957-9
|View full text |Cite
|
Sign up to set email alerts
|

Positive associations between sex hormones, bone metabolism and cognitive impairment in Chinese oldest-old females

Abstract: Purpose With a rapid increase in older adults, progressive impairment in cognitive function has become an increasing concern owing to high social and economic burdens. The current study was designed to investigate the associations of sex hormones and bone metabolism with cognitive impairment (CI) in Chinese oldest-old females. Methods There were 396 oldest-old females from the China Hainan Oldest-old Cohort Study (CHOCS). Following standardized pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…A supplementing with 25(OH)D3 might increase serum 25(OH)D3 and testosterone level in obese mice 53 . Bioavailable testosterone presented a positive association of cognitive function in older men 54 , while prolactin, progesterone and estradiol might have deleterious effects on cognitive function in older females after menopause 55 , 56 . However, the number of patients in our subgroup is relatively limited, and the insignificance may be due to the small sample size.…”
Section: Discussionmentioning
confidence: 94%
“…A supplementing with 25(OH)D3 might increase serum 25(OH)D3 and testosterone level in obese mice 53 . Bioavailable testosterone presented a positive association of cognitive function in older men 54 , while prolactin, progesterone and estradiol might have deleterious effects on cognitive function in older females after menopause 55 , 56 . However, the number of patients in our subgroup is relatively limited, and the insignificance may be due to the small sample size.…”
Section: Discussionmentioning
confidence: 94%
“…This study found that psychological resilience played a protective role in survival outcomes for the oldest-old in China. The oldest-old often face various sources of stress, such as health issues related to physical frailty, economic burdens associated with caregiving, and social isolation ( 37 , 38 ). These negative events require a strong psychological resilience to adopt appropriate solutions.…”
Section: Discussionmentioning
confidence: 99%